Application of Azido Esters as Energetic Plasticizers for LOVA Propellant Formulations. Issue 6 (9th October 2013) - Kumari, Dimple; Yamajala, K. Durga Bhaskhar; Singh, Haridwar; Sanghavi, Rakesh R.; Asthana, Shri N.; Raju, K.; Banerjee, Shaibal
Abstract The study of a cyclotrimethylene trinitramine‐based low vulnerable ammunition (LOVA) propellant having cellulose acetate (CA) and nitrocellulose (NC) combinations as binders is described herein. Two propellant compositions (1 and 2) were prepared by replacing the non energetic plasticizer triacetin (TA) with the novel tetraazido ester plasticizers tetraazido malonate and tetraazido glutarate, respectively, and their ballistic, mechanical, and thermal properties were studied. Both compositions 1 and 2 showed thermal stability up to 200 °C with a heat release of 1752.81 and 1774.34 J g−1, respectively. Both compositions have high impact insensitivity (h50: 39 cm), friction insensitivity up to 36 kg, and an ignition temperature greater than 250 °C. The flame temperatures of 1 and 2 are 3164 and 3243 K with linear burn rate coefficients of 0.117 and 0.122 cm s−1 MPa−1, respectively. Similar percentage elongations at three different temperatures (−20 °C, +27 °C, and +55 °C) conditions were recorded for both compositions.